Strengthening the delivery of integrated care for individuals experiencing serious mental illness within mental health settings: a qualitative description of health provider perspectives - Munazzah Ambreen; Christopher Canning; Brian Lo; Sri Mahavir Agarwal; Amer M. Burhan; David Castle; M. Elisabeth Del Giudice; Barna Konkolÿ-Thege; Louis Liu; Osnat C. Melamed; Frank Sirotich; Sanjeev Sockalingam; et al. (BMC Psychiatry)
Abstract Background Individuals experiencing serious mental illness (SMI) have higher rates of comorbid physical health conditions, poorer associated health outcomes, and die on average 10–20 years earlier than the general population. They encounter multiple barriers to accessing appropriate physical health care in many countries, including Canada, where policies and practices to promote integrated care delivery to this population remain scant. This qualitative study aimed to explore health provider perspectives and experiences with integrated physical and mental health care within mental health settings in Canada, in efforts to address the health needs of this population. Methods This qualitative descriptive study involved conducting individual semi-structured interviews with 13 health administrators and four focus groups with 15 clinicians between July 2023 and April 2024. The data analysis team, inclusive of individuals with SMI, used thematic analysis to identify overarching themes that capture participants’ perspectives on and experiences with delivering integrated physical and mental health care within mental health settings in Canada, including their clinical practices and organizational contexts. Results We identified four themes in participant narratives: (1) the need for integrated care delivery within mental health settings; (2) organizational readiness for integrated care; (3) moving integration forward: addressing challenges; and (4) leveraging opportunities to advance integrated care. Both participant groups highlighted challenges with fragmented healthcare services, emphasized the urgent need for policies, practices and guidelines that support person-centered, comprehensive care within mental health settings, and called for engaging people with living/lived experience and family members in service redesign. Conclusion Findings underscore the importance of accelerating efforts to promote integrated health care delivery for adults with SMI within mental health settings, and of implementing policies that address health disparities for this population in the Canadian context. Clinical trial number Not Applicable.